Optimization of sugarcane straw as a solid biofuel for thermochemical processes by water leaching pretreatment - Assureira, Estela; Assureira, Marco (International Journal of Renewable Energy Development, 2025)
Sugarcane straw, an abundant agricultural waste, has considerable potential as a renewable fuel due to its energy content, sustained generation, and CO2 neutrality but its direct utilization is limited by its high levels of ash, alkalis, S, Cl contents that cause severe slagging, fouling, and corrosion in boilers, as well as the harmful emissions released during combustion. To improve the fuel properties of sugarcane straw, a leaching pretreatment with distilled water was developed and applied to the residue under controlled conditions to evaluate the effects of water temperature, residence time and agitation of the leachate on the removal effectiveness of soluble ash-forming components. The leaching process was carried out in batches, maintaining a solid-to-liquid ratio of 1:30, and a feedstock size of 0.5–2 cm. Various combinations of temperature, residence time, and leachate agitation condition were tested to optimize the process. The optimal condition was established at 80 °C and 20 min with continuous agitation, which was applied to the residue, achieving reductions of 38.46% in ash, 78.26 in Cl, 57.14% in S, 9.09% in N, 54.61% in K2O, and 58.22% in Na2O, along with an increase in the high heating value, which reached 18.4 MJ/kg. These improvements reduce slagging, fouling and corrosion tendency, as indicated by lower predictive indices and higher ash fusion temperature reflected in the ternary phase diagram, and enhanced energy content. The improvements achieved make the washed sugarcane straw suitable for industrial biofuel applications, reducing issues associated with ash and emissions and providing higher energy content. The water leaching pretreatment also represents a valuable contribution since it can be easily replicated, and the upgraded residue has been valorized by being converted into a clean and sustainable fuel.